Respuesta :

(3)^3 - 2(5)^2 - 3(3)^3 + -3^4
27-100-729-81 =
-883

Answer:

The value of the expression for the given values of x,y and z is:

                          -23

Step-by-step explanation:

The algebraic expression is given by:

         [tex]x^3-2y^2-3x^3+z^4[/tex]

We are asked to evaluate the value of the expression when

[tex]x=3\ ,\ y=5\  and\ z=-3[/tex]

Now, putting these values in the given expression we have:

[tex]=3^3-2(5)^2-3(3)^3+(-3)^4\\\\=3^3-2(5)^2-(3)^4+(3)^4\\\\=27-2\times 25+0\\\\=27-50\\\\=-23[/tex]

       Hence, the answer is: -23